Avaliação da dimetil arginina assimétrica plasmática e da dilatação fluxo-mediada da artéria braquial em gestantes com fatores de risco para o desenvolvimento de pré-eclâmpsia - Juliana Eugenio de Souza (2016)
Pre-eclampsia is a major cause of maternal and fetal morbidity and mortality. Although it has not been clarified its pathophysiology, systemic endothelial dysfunction is one of the main characteristics of this syndrome. The objective of our study were to assess some of the markers of endothelial dysfunction, the asymmetric dimethylarginine serum levels and the test of flow-mediated dilation of the brachialartery, in a group of pregnant women with risk factors for development of this complication and to check for correlation between asymmetric dimethylarginine values with the evaluated demographic characteristics. The sample was selected in the prenatal service Jenny Faria do Hospital das Clínicas da Universidade Federal de Minas Gerais with pregnant women who presented in the clinic and who possessed a risk factor for development of Pre-Eclampsia. For determination of serum levels of asymmetric dimethylarginine, it was used the ADMA-ELISA (DLDDiagnostika GMBH®). Of the 48 patients evaluated, 12 (25%) developed Pre- Eclampsia and 36 (75%) remained normotensive. In the group of patients with Pre- Eclampsia, the median level of asymmetric dimethylarginine obtained was 0.422 and the average expansion was 25.43% ± 11.70%. Of the patients who remained normotensive throughout gestation, the median level of asymmetric dimethylargininewas found to be 0.583 and the average obtained dilatation was 15.91% ± 8.09. There was no significant difference between the serum levels of asymmetric dimethylarginine among the groups (p value 0,082) but there was significant difference between the measurements of flow-mediated dilatation (p value 0,004). Only there was a significant correlation between asymmetric dimethylarginine serum levels and gestational age at which the birth occurred (-0.687; p 0.014). These findings refer to dosing between gestational age 16-29 weeks probably inadequate toverify this pathophysiological component of Pre-Eclampsia.